Scale inhibitor for deep coal bed gas fracturing and integrated fracturing fluid preparation method

By using special scale inhibitors in deep coalbed methane fracturing fluid, the problem of poor viscosity effect of fracturing fluid under high mineralization and high calcium and magnesium ion content is solved, and efficient reuse and stability of fracturing retrieval fluid is achieved.

CN119736073APending Publication Date: 2025-04-01CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411685814.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing salt-resistant fracturing liquid system has poor viscosity effect in deep coal reservoir fracturing reflux fluid with high mineralization and high calcium and magnesium ion content, and cannot meet the requirements of large-scale fracturing process, resulting in the difficulty of reusing reflux fluid.

Method used

Using a scale inhibitor for deep coalbed methane gas fracturing, it is prepared by sodium carboxymethylcellulose, acrylamide, acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid and initiator compositions (ammonium persulfate and sodium bisulfite). The scale inhibitor has excellent viscosity-acting effect and the ability to disperse insoluble calcium and magnesium ions, preventing or interfering with its precipitation and scaling.

Benefits of technology

The reuse of deep coalbed methane fracturing re-discharge liquid is achieved, and the scale resistance rate can reach more than 90%, effectively improving the salt resistance and stability of the fracturing liquid and reducing mining costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736073A_ABST
    Figure CN119736073A_ABST
Patent Text Reader

Abstract

The invention discloses a scale inhibitor for deep coal bed gas fracturing and a preparation method of integrated fracturing fluid. The scale inhibitor is prepared from the following raw materials in parts by mass: 1 part of sodium carboxymethyl cellulose; 4.5 to 5.5 parts of acrylamide, acrylic acid, and 2-acrylamide-2-methylpropanesulfonic acid; the initiator composition is prepared from the following components in parts by weight: 0.1 to 0.12 part of ammonium persulfate and 0.05 to 0.06 part of sodium hydrogen sulfite. The integrated fracturing fluid is prepared from the following raw materials in percentage by mass: 1.2 to 2 percent of concentrated solution, 0.1 to 0.3 percent of scale inhibitor and the balance of water. The concentrated solution comprises the following components in percentage by mass: 58-65% of white oil; 1.5%-2.5% of a stabilizer; 0.3%-0.8% of an activating agent; 30-35% of a resistance reducing agent, wherein the content of the resistance reducing agent in the fracturing fluid is greater than or equal to 0.4%; and 2.5-4.5% of a phase inversion agent. The scale inhibition rate of the scale inhibitor can reach 90% or above, and the scale inhibitor can be applied to fracturing fluid to realize repeated utilization of deep coal bed gas fracturing flow-back fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of deep coalbed methane development, and in particular to a scale inhibitor for deep coalbed methane fracturing and a method for preparing an integrated fracturing fluid. Background Art

[0002] Large-scale fracture network fracturing technology is characterized by large liquid volume, large sand volume, and large displacement, resulting in a huge amount of return fluid. The return fluid volume of a single horizontal well exceeds 10,000 cubic meters, which is more than 6 times that of the past tight gas horizontal wells. Due to the high mineralization of deep coal reservoir fracturing return fluid and high calcium and magnesium ion content, the overall mineralization exceeds 100,000 ppm on average, and the calcium ion accounts for a high proportion, with an average of 14.97% and an average content of 23878 mg / L. In order to achieve the reuse of return fluid, fracturing return fluid can be subjected to a series of water treatment technologies, such as oxidation degelation technology, enhanced coagulation technology, nanofiltration technology efficient coupling, oxidation + flocculation technology, desalination technology, etc., so as to improve the water quality of fracturing return fluid. However, for large-scale fracturing technology of deep coalbed methane, the treatment of return fluid will cause a sharp increase in fracturing costs, and the effect of improving water quality is also extremely limited. Therefore, the use of salt-resistant thickeners is one of the key methods to solve this problem.

[0003] At present, the salt-resistant polymers in the salt-resistant fracturing fluid system have poor viscosity effect under high mineralization, especially in fracturing return fluids with high calcium and magnesium ion content, and cannot meet the requirements of large-scale fracturing processes. As a result, the existing fracturing return fluid reuse technology is difficult to apply in the deep coalbed methane on the eastern edge of the Ordos Basin. Therefore, the reuse of fracturing return fluid has become a problem. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a scale inhibitor for deep coalbed methane fracturing and a method for preparing an integrated fracturing fluid. The scale inhibition rate of the scale inhibitor of the present invention after application can reach more than 90%, so that the reuse of deep coalbed methane fracturing return fluid can be achieved.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A scale inhibitor for deep coalbed methane fracturing is prepared by using the following raw materials in parts by mass:

[0007] 1 part of sodium carboxymethyl cellulose;

[0008] 4.5-5.5 parts of acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid;

[0009] The initiator composition comprises ammonium persulfate and sodium bisulfite, wherein the ammonium persulfate is 0.1-0.12 parts and the sodium bisulfite is 0.05-0.06 parts.

[0010] Compared with the prior art, the present invention has the following beneficial effects:

[0011] 1. The scale inhibitor of the present invention is used in fracturing fluid, which is suitable for the reuse of fracturing flowback fluid from deep coal reservoirs with high mineralization and high calcium and magnesium ion content. It not only has excellent viscosity-generating effect, but also can effectively disperse inorganic salts of insoluble calcium and magnesium ions, prevent or interfere with their precipitation and scaling. The scale inhibition rate after application can reach more than 90%, so that the reuse of deep coalbed methane fracturing flowback fluid can be achieved.

[0012] 2. The initiator composition used is divided into an oxidant part and a reductant part. The oxidant part is ammonium persulfate and the reductant part is sodium bisulfite. Ammonium persulfate is used to dissolve and evenly disperse in the reaction system in advance, and sodium bisulfite is used to initiate free radical polymerization. The initiator composition can allow the redox reaction to produce more free radicals, and then graft copolymerize more useful functional groups, thereby improving the overall output and yield, thereby effectively improving the scale inhibition rate of the scale inhibitor.

[0013] 2. The scale inhibitor of the present invention is a relatively clean system, especially in the high temperature and high pressure environment of deep coalbed methane exploitation, it is relatively easy to degrade and is less harmful to the formation than large molecular polymers.

[0014] As a preferred embodiment of the present invention, the usage ratio of acrylamide, acrylic acid (AA) and 2-acrylamide-2-methylpropanesulfonic acid is 3:1:1.

[0015] As a preferred embodiment of the present invention, the method of the following steps is adopted to prepare:

[0016] S1: Add sodium carboxymethyl cellulose into deionized water, and then place in a constant temperature water bath and stir to dissolve;

[0017] S2: Weigh acrylamide, acrylic acid, and 2-acrylamide-2-methylpropanesulfonic acid, add distilled water to dissolve, and then adjust the pH to neutral with NaOH solution;

[0018] S3: When the temperature of S1 is constant, add the solution prepared in S2, evacuate and introduce nitrogen;

[0019] S4: Weigh ammonium persulfate and add it to distilled water, dissolve it and pour it into S3, evacuate the vacuum, and introduce nitrogen;

[0020] S5: Weigh sodium bisulfite and add it to distilled water, dissolve it and pour it into S4, evacuate it, introduce nitrogen, heat it to 20°C, react at this temperature for a certain period of time, and then cool it to room temperature;

[0021] S6: After the reaction is completed, the polymer product is scraped off, dried in a vacuum oven for 7-8 hours to constant weight, and then taken out and crushed into 40-60 mesh.

[0022] The preparation method of this scheme is simple, and the prepared scale inhibitor is suitable for the reuse of deep coal reservoir fracturing return fluid with high mineralization and high calcium and magnesium ion content. It not only has excellent viscosity-forming effect, but also can effectively disperse inorganic salts of insoluble calcium and magnesium ions, prevent or interfere with their precipitation and scaling. The scale inhibition rate after application can reach more than 90%, so that the reuse of deep coalbed methane fracturing return fluid can be realized.

[0023] As a preferred embodiment of the present invention, the time interval for adding the ammonium persulfate and sodium bisulfite is 4.5-6.5 min. In this scheme, the time interval for adding the ammonium persulfate and sodium bisulfite is controlled within the above range, and the yield and output are higher overall. With the increase of the advance addition time, the dissolution distribution in the reaction system is more uniform, and a multi-stage chain initiation can be formed, resulting in a higher grafting rate. Moreover, a long time interval is not conducive to the generation of free radicals by the redox reaction.

[0024] As a preferred embodiment of the present invention, the reaction time of step S5 is 5-6h. In this scheme, the reaction time of step S5 is controlled within the above range, and the scale inhibition rate of the polymer product can reach more than 95%, but further extending the reaction time will no longer have a significant effect on the scale inhibition effect. Too long a reaction time may even cause partial hydrolysis of the CMC body structure, resulting in a decrease in the scale inhibition rate.

[0025] The integrated fracturing fluid preparation method comprises the following raw materials by mass fraction: 1.2-2% of concentrated liquid, 0.1-0.3% of scale inhibitor, and the rest is water.

[0026] The concentrate comprises, by mass percentage: 58-65% white oil; 1.5-2.5% stabilizer; 0.3-0.8% activator; 30-35% drag reducing agent, and the content of the drag reducing agent in the fracturing fluid is ≥0.4%; 2.5-4.5% phase inversion agent;

[0027] The concentrate is added in the following order: white oil, stabilizer, activator, drag reducer, phase transfer agent, and each ingredient is stirred and mixed evenly after being added.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The integrated fracturing fluid prepared by the present invention is suitable for the reuse of fracturing flowback fluid from deep coal reservoirs with high mineralization and high calcium and magnesium ion content. It not only has excellent viscosity-forming effect, but also can effectively disperse inorganic salts of insoluble calcium and magnesium ions, prevent or interfere with their precipitation and scaling. The scale inhibition rate after application can reach more than 90%, so that the reuse of deep coalbed methane fracturing flowback fluid can be achieved.

[0030] 2. Prepare according to the above-mentioned adding order of this scheme, add the activator after adding the stabilizer, the stabilizer forms a gel in the white oil, so that the solvent is evenly mixed after adding the drag reducing agent, which is conducive to the dissolution of the drag reducing agent, so that the stability of the finally prepared integrated fracturing fluid is good.

[0031] 3. The present invention controls the addition of 58-65% white oil to the concentrated liquid. The present invention has found in the study that when the white oil content is low, it may be because the oil phase content is too little, so that the stabilizer and the drag reducer cannot be fully hydrated, so they are quickly separated. The present invention has found in the study that when the white oil content is 58-65%, the stability of the finally prepared integrated fracturing fluid is higher; secondly, the present invention has also found in the study that when the drag reducer is controlled in the range of 30-35%, and the content of the drag reducer in the fracturing fluid is controlled to be ≥0.4%, the integrated fracturing fluid has good fluidity and high viscosity, and has better comprehensive performance; in addition, the stability of the integrated fracturing fluid in this scheme is also affected by the type and content of the stabilizer, while whether the stabilizer can work is determined by the activator, so the stabilizer and the activator are correlated in the stability of the integrated fracturing fluid, and the integrated fracturing fluid using the above components and specific ratios has better stability as a whole.

[0032] As a preferred embodiment of the present invention, the stabilizer is BP-138, the activator is isopropanol, the phase inversion agent is octylphenol polyoxyethylene ether, and the drag reducing agent is modified polyacrylamide. In this solution, the stabilizer is BP-138, the activator is isopropanol, and the prepared integrated fracturing fluid has lower stratification and better stability; the phase inversion agent is octylphenol polyoxyethylene ether, which can improve the solubility and viscosity of the integrated fracturing fluid.

[0033] As a preferred embodiment of the present invention, the following components are included by mass fraction: 58% white oil, 2.5% stabilizer BP-138, activator isopropanol is 20% of the stabilizer content, 4% phase inversion agent, 35% drag reducing agent. In this solution, the integrated fracturing fluid using the above components and specific ratios has the best overall stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the effect of APS addition time on the yield and yield when the reaction pH is 4.3;

[0035] Figure 2 This is the effect of APS addition time on yield and yield when the reaction pH is 7.0;

[0036] Figure 3 This is the effect of polymerization reaction time on scale inhibition rate when the reaction pH value is 4.3;

[0037] Figure 4This is the effect of polymerization reaction time on scale inhibition rate when the reaction pH value is 7.0;

[0038] Figure 5 It is a stratified diagram of the screening experiment for types of stabilizers and activators;

[0039] Figure 6 This is a physical picture of the integrated suspension system after centrifugation at different additive dosages;

[0040] Figure 7 This is the viscosity change diagram of 0.5% drag reducing agent in Na salt and Ca mineralized water with different mineralization degrees;

[0041] Figure 8 This is the viscosity change diagram of 200,000 ppm Na salt and Ca mineralized water under different dosages of drag reducer;

[0042] Fig. 9 This is a graph showing the apparent viscosity change of 0.5% drag reducing agent at different mineralization levels. DETAILED DESCRIPTION

[0043] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions and illustrations therein are essentially used for illustration purposes rather than for limiting the present invention.

[0044] Example 1

[0045] This embodiment discloses a scale inhibitor for deep coalbed methane fracturing, which is prepared using the following raw materials:

[0046] Sodium carboxymethyl cellulose 0.5 g;

[0047] 1.5 g acrylamide, 0.5 g acrylic acid, 0.5 g 2-acrylamide-2-methylpropanesulfonic acid;

[0048] The initiator composition comprises ammonium persulfate and sodium bisulfite, wherein the ammonium persulfate is 0.07 g and the sodium bisulfite is 0.035 g.

[0049] Prepared by the following steps:

[0050] S1: In a round-bottom flask, add 0.5 g sodium carboxymethyl cellulose (CMC) to 40 mL deionized water, and then place the beaker in a constant temperature water bath and stir to dissolve for about 30 min;

[0051] S2: Weigh 1.5 g acrylamide, 0.5 g acrylic acid, and 0.5 g 2-acrylamide-2-methylpropanesulfonic acid into a small beaker, add 2.5 g distilled water to dissolve, and then adjust the pH to 7 with 8 mol / L NaOH solution;

[0052] S3: When the temperature of S1 is constant, pour the solution in the small beaker of S2 into the flask, evacuate the flask, and introduce nitrogen for about 10 minutes;

[0053] S4: Weigh 0.07g of ammonium persulfate in a small beaker, add 1.5mL of distilled water, dissolve and pour into S3 flask, evacuate, introduce nitrogen, and record the time of adding ammonium persulfate;

[0054] S5: Weigh 0.035g sodium bisulfite in a small beaker, add 1.5mL distilled water, dissolve and pour into S4 flask, add ammonium persulfate and sodium bisulfite at an interval of 5min, evacuate, introduce nitrogen, heat to 20℃, react at constant temperature for 5h, and then cool to room temperature;

[0055] S6: After the reaction is completed, the polymer product is scraped off, dried in a vacuum oven for 7-8 hours to constant weight, and then taken out and crushed into 40-60 mesh.

[0056] Experimental study on the effects of pH value and initiator addition time on reaction yield

[0057] Due to the reaction rate of the redox reaction during graft copolymerization and the molecular weight of the polymerization and the pH value, the time of adding the oxidant part and the reductant part of the initiator composition separately is closely related. In the present embodiment, the effect of pH value and the advance addition time of ammonium persulfate (APS) on the reaction yield was tested, and the other conditions were the same as in Example 1 (Serial No. 9 is Example 1).

[0058] Table 1 Effect of advance addition time of ammonium persulfate (APS) on yield and yield (pH = 4.3)

[0059]

[0060] When the reaction pH is 4.3 and the reaction temperature is 20°C, the effect of APS addition time on the yield and output is as follows: Figure 1 As shown in Table 1, when the reaction pH value is 4.3, with the increase of the advance addition time of APS, the output and yield show a fluctuating upward trend, and the maximum yield reaches 127.6%. This shows that when the oxidant part and the reductant part are added separately and the time is extended, it is beneficial to increase the yield to a certain extent. This is because APS has no initiation effect at low temperature, and with the increase of advance addition time, its dissolution distribution in the reaction system is more uniform, which can form multi-stage chain initiation and bring higher grafting rate.

[0061] When the reaction pH value is 7.0, the effect of APS addition time on the yield and yield is as follows: Figure 2 Compared with Table 2. Figure 1As shown in Table 1, when the pH value of the system is 7.0, the overall yield and rate are significantly improved, which indicates that the graft copolymerization reaction is more favorable under neutral conditions. As the APS addition time increases, the yield and rate increase first and then decrease, and the yield reaches a maximum of 2.954g at about 5 minutes, which indicates that the stirring time of a single APS is too long, which is not conducive to the production of free radicals by the redox reaction.

[0062] Table 2 Effect of advance addition time of ammonium persulfate (APS) on yield and yield (pH = 7.0)

[0063]

[0064]

[0065] Polymerization reaction time experiment

[0066] In Example 1, in a 40 mL reaction system, the amount of sodium carboxymethyl cellulose (CMC) is 0.5 g, the total amount of acrylamide, acrylic acid and 2-acrylamide-2-methylpropane sulfonic acid monomers is 2 g, the total amount of initiator ammonium persulfate (APS) and sodium bisulfite is 0.105 g, the reaction temperature T=20°C, and the other conditions are the same as in Example 1. The polymerization reaction time is adjusted to obtain the optimal synthesis conditions (Sequence No. 7 is Example 1).

[0067] Table 3 Effect of polymerization reaction time on scale inhibition rate (pH = 4.3)

[0068]

[0069] from Figure 3 As shown in Table 3, when the pH value is 4.3, as the polymerization reaction time increases, the scale inhibition rate first decreases and then increases, reaching a maximum of 96.04% at 5 hours. This is because the reaction time is too short, the reaction sites of the grafting reaction are not fully involved, and there are fewer carboxyl and sulfonic acid groups grafted on the CMC main chain. Although the scale inhibition performance is improved compared with the unmodified CMC, it has not reached the highest level. After 5 hours, the reaction is basically completed. The scale inhibition rate does not change significantly as the reaction time continues to increase.

[0070] Table 4 Effect of polymerization reaction time on scale inhibition rate (pH = 7.0)

[0071]

[0072]

[0073] from Figure 4As shown in Table 4, when the pH value of the system is 7.0, as the reaction time increases from 5h to 8h, the scale inhibition rate of the polymer product decreases from 99.04% to 92.31%. During this period, the scale inhibition rate of the graft copolymer product continued to decline and only reached the maximum value when the reaction time was 5h. Figure 3 The analysis in Table 4 shows that the optimal polymerization reaction time is 5h, at which time the polymerization reaction is basically completed, and further extending the reaction time has no significant effect on the scale inhibition effect. Over-long reaction time may even cause partial hydrolysis of the CMC structure. Therefore, considering comprehensively, the reaction time in step S5 of the present invention is controlled to 5-6h to ensure the best scale inhibition rate of the polymer product.

[0074] Example 2

[0075] This embodiment discloses an integrated fracturing fluid preparation method, which includes the following raw materials by mass fraction: 1.43% concentrate, 0.1% scale inhibitor, and the rest water.

[0076] The concentrate includes by mass percentage:

[0077] White oil 58%; stabilizer 2.5%; activator 0.5%; drag reducing agent 35%; phase inversion agent 4%;

[0078] Add the following ingredients in the following order: white oil, stabilizer, activator, resistance reducer, phase transfer agent, and scale inhibitor. Stir and mix evenly after adding each ingredient.

[0079] In this embodiment, the stabilizer is BP-138, the activator is isopropanol, the phase transfer agent is octylphenol polyoxyethylene ether, and the drag reducing agent is modified polyacrylamide, which are purchased from Sichuan Shenhe New Materials Co., Ltd.

[0080] Example 3

[0081] The difference between this embodiment and the embodiment 1 is that the concentrated liquid comprises, by mass percentage, 65% white oil; 2% stabilizer; 0.75% activator; 30% drag reducing agent; and 2.75% phase inversion agent.

[0082] Screening experiments for stabilizer and activator types

[0083] In this experiment, five bentonite stabilizers (FHD-130D, BP-138, BP-922, HFGEL-136C, FHGEL-979) were selected and configured into an integrated suspension (including 65% white oil, 2% stabilizer, 30% drag reducer, 2.75% phase transfer agent, 0.75% activator (35% of the stabilizer addition amount). After stirring evenly, 10 ml of each was taken into a centrifuge tube, and the stratification was observed after centrifugation at 3500r / min for 15 minutes.

[0084] like Figure 5As shown, the selection of FHGEL-979 corresponds to Figure 5 In the first test tube in the first, second, third, and fourth pictures, HFGEL-136C corresponds to Figure 5 In the second test tube in the first, second, third, and fourth pictures, the corresponding FHD-130D is Figure 5 In the third test tube in the first, second, third, and fourth pictures, the corresponding BP-922 is Figure 5 In the first, second, third, and fourth test tubes, BP-138 corresponds to Figure 5 In the last test tube in the first, second, third, and fourth pictures, and Figure 6 The lower the stratification, the better the stability of the suspension, which means the better the stabilizer used in the suspension. It can be seen that stabilizer BP-138 and polar activator isopropanol have the best stability, so BP-138 and isopropanol are selected.

[0085] Drag reducing agent content selection experiment

[0086] In this experiment, the drag reducing agent content of 25%, 30%, 35%, and 40% was selected to prepare the suspension. The other components of the suspension are shown in Table 5 below. The suspension system was prepared in the order of adding white oil, stabilizer, activator, drag reducing agent, and phase inversion agent, and the fluidity of the integrated suspension was observed, and the dissolution rate and viscosity in water were measured. Although the viscosity of the solid content of 40% is high, the fluidity of the suspension is poor, while the suspension with 35% drag reducing agent content has good fluidity and high viscosity. Considering comprehensively, the amount of drag reducing agent added is controlled at 30-35%.

[0087] Table 1 Effect of drag reducing agent content

[0088]

[0089] Screening experiment of phase inversion agent

[0090] The experiment used two phase inversion agents, nonylphenol polyoxyethylene ether (NP-10) and octylphenol polyoxyethylene ether (OPE-10). The suspension system was prepared in the order of adding white oil, stabilizer, activator, drag reducer, and phase inversion agent, and then 4.0g of the suspension was added to a beaker containing 400ml of water, the dissolution rate was observed, and its viscosity was measured. The results showed that the solubility and viscosity of the suspension prepared by adding OPE-10 were better than those of the suspension prepared by NP-10, so the phase inversion agent OPE-10 was selected as the phase inversion agent.

[0091] Table 2 Effect of phase inversion agent type

[0092]

[0093] Experiment on optimizing the content of stabilizer, activator and phase inversion agent

[0094] The stability of the integrated suspension is determined by the type and content of the stabilizer, while whether the stabilizer can be effective is determined by the activator. Therefore, the stabilizer and the activator are correlated in the stability of the integrated suspension. This experimental design uses orthogonal experiments to screen the optimal content of stabilizers, activators and phase transfer agents. The content of the drag reducer is fixed at 35%, and the optimal content of the stabilizer, activator and phase transfer agent is screened. The rest is white oil. The suspension system is prepared in the order of adding white oil, stabilizer, activator, drag reducer and phase transfer agent.

[0095] Table 3 Preferred content of stabilizer, activator and phase inversion agent

[0096]

[0097] Table 4 The amount of additives represented by the corresponding numbers

[0098]

[0099] Take 10 ml of the integrated suspension and centrifuge it at 2500 rpm for 30 min to observe the stability of the suspension. Figure 6 As shown, the suspension system prepared by group 13 has the highest stable interface, which indicates that this suspension system has the best stability. The formula of this suspension system: 58% white oil, 2.5% stabilizer BP-138, activator isopropyl alcohol is 20% of the stabilizer content, 4% phase inversion agent, 35% drag reducing agent.

[0100] Salt resistance test

[0101] The salt resistance of the integrated fracturing fluid prepared by the method of Example 2 was tested.

[0102] like Figure 7 As shown, the integrated fracturing fluid has a greater tolerance to sodium salt (50,000 ppm) than calcium salt (10,000 ppm), but as the mineralization increases, the viscosity in sodium salt can still reach 50 mP.s, and the viscosity in calcium salt can reach 38 mP.s.

[0103] like Figure 8 As shown, in 200,000 ppm of Na salt with a mineralization degree, when the amount of drag reducing agent in the integrated fracturing fluid is above 0.4%, its apparent viscosity is greater than 72 mPa.s. In 200,000 ppm of Ca salt with a mineralization degree, when the amount of drag reducing agent is above 0.4%, its apparent viscosity is greater than 27 mPa.s.

[0104] like Fig. 9As shown in the figure, the apparent viscosity of 0.5% drag reducer in integrated fracturing fluid at different salinities was tested. It can be found that above 40,000 salinities, the viscosity of the drag reducer solution remains almost unchanged. In brine with a salinity of 200,000 ppm (calcium ion content of 30,000 ppm and magnesium ion content of 5,000 ppm), the viscosity is > 40 mPa.s, which meets the needs of on-site use.

[0105] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A scale inhibitor for deep coalbed methane fracturing, characterized in that: The following raw materials were used in parts by mass: 1 part of sodium carboxymethyl cellulose; 4.5-5.5 parts of acrylamide, acrylic acid and 2-acrylamide-2-methylpropanesulfonic acid; The initiator composition comprises ammonium persulfate and sodium bisulfite, wherein the ammonium persulfate is 0.1-0.12 parts and the sodium bisulfite is 0.05-0.06 parts.

2. The scale inhibitor for deep coalbed methane fracturing according to claim 1, characterized in that: The usage ratio of acrylamide, acrylic acid (AA) and 2-acrylamide-2-methylpropanesulfonic acid is 3:1:

1.

3. The scale inhibitor for deep coalbed methane fracturing according to claim 2, characterized in that: Prepared by the following steps: S1: Add sodium carboxymethyl cellulose into deionized water, and then place in a constant temperature water bath and stir to dissolve; S2: Weigh acrylamide, acrylic acid, and 2-acrylamide-2-methylpropanesulfonic acid, add distilled water to dissolve, and then adjust the pH to neutral with NaOH solution; S3: When the temperature of S1 is constant, add the solution prepared in S2, evacuate and introduce nitrogen; S4: Weigh ammonium persulfate and add it to distilled water, dissolve it and pour it into S3, evacuate the vacuum, and introduce nitrogen; S5: Weigh sodium bisulfite and add it to distilled water, dissolve it and pour it into S4, evacuate it, introduce nitrogen, heat it to 20°C, react at this temperature for a certain period of time, and then cool it to room temperature; S6: After the reaction is completed, the polymer product is scraped off, dried in a vacuum oven for 7-8 hours to constant weight, and then taken out and crushed into 40-60 mesh.

4. The scale inhibitor for deep coalbed methane fracturing according to claim 3, characterized in that: The time interval for adding the ammonium persulfate and sodium bisulfite is 4.5-10 minutes.

5. The scale inhibitor for deep coalbed methane fracturing according to claim 3, characterized in that: The reaction time of step S5 is 5-6h.

6. An integrated fracturing fluid preparation method, characterized in that: It includes the following raw materials by mass fraction: 1.2-2% concentrate, 0.1-0.3% scale inhibitor, and the rest is water; The concentrate includes, by mass percentage: 58-65% white oil; 1.5-2.5% stabilizer; 0.3-0.8% activator; 30-35% drag reducing agent, and the content of the drag reducing agent in the fracturing fluid is ≥0.4%; 2.5-4.5% phase inversion agent; The concentrate is added in the following order: white oil, stabilizer, activator, drag reducer, phase transfer agent, and each ingredient is stirred and mixed evenly after being added.

7. The integrated fracturing fluid preparation method according to claim 6, characterized in that: The stabilizer is BP-138, the activator is isopropyl alcohol, the phase transfer agent is octylphenol polyoxyethylene ether, and the drag reducing agent is modified polyacrylamide.

8. The method for preparing an integrated fracturing fluid according to claim 6, characterized in that: The concentrate includes, by mass percentage: 58% white oil, 2.5% stabilizer BP-138, activator isopropanol accounting for 20% of the stabilizer content, 4% phase transfer agent, and 35% drag reducing agent.